(untitled) (World Bulletin of Management and Law, 2023)
The provisions for fulfilling demands for compensation, as a result of unlawful acts by the authorities based on Article 3 PP Number 43 of 1991 concerning Compensation and Procedures for its Implementation in the State Administrative Court have not been eligible so that the compensation decision from the court does does not provide benefits and does not resolve those problems that arise. This research aims to study and analyze the concepts and constructions in providing compensation due to unlawful acts committed by government agencies and/or officials. The method used is normative juridical research through statutory approaches (statute approach), case approach (case approach) and comparative approach (comparative approach). The results of the research indicate that there is a legal vacuum, so that it is necessary to expand the authority of the Administrative Court through revisions to the Law on State Administrative Courts, supplemented by an Act against the law compensation mechanism carried out by the Government